(Studi Deskriptif) Implementasi Pelayanan Bimbingan dan Konseling - Wahyuni, Dyah Ayu S; Anni, Catharina Tri (Universitas Negeri Semarang, 2016)
The purpose of this study was to describe the implementation of BK services in Semarang whether all services can be implemented by counselor with qualitative. descriptive study is about the implementation of BK services that include direct services such as the assignment of counselor, RPLBK used as a reference implementation of the service, and indirect services such as directing students through services such as media, teachers held consultations BK, counselor and cooperation with stakeholders, samples are teachers who carry out services BK. Respondents are counselors and school personnel as supporting data sources, data collection techniques using interview, observation and documentation. The validity of the data used data triangulation. Data Analysis namely data collection, data reduction, data display and conclusion. Results of research tasks counselor in implementing services classical, individuals and groups are still less than the maximum hampered by the allocation of time, the structure in RPLBK not much has changed and every year almost the same, directing students through various forms of media, but in its implementation counselor still less attention to media such boards are rarely updated guidance and sharing boxes that were not appropriate in its implementation, consultations counselor not yet fully done together stakeholders